2008
DOI: 10.1007/s10096-008-0524-4
|View full text |Cite
|
Sign up to set email alerts
|

Low incidence of antibiotic resistance among invasive and nasopharyngeal isolates of Streptococcus pneumoniae from children in rural Philippines between 1994 and 2000

Abstract: The purpose of this study was to determine the prevalence of acquired antimicrobial resistance in Streptococcus pneumoniae isolated from nasopharyngeal swabs and blood and cerebrospinal fluid (CSF) specimens of 3,028 children hospitalized with signs or symptoms of pneumonia, sepsis, or meningitis in rural Philippines between 1994 and 2000. Pneumococci were identified using standard methods, serotyped, and their susceptibility to oxacillin, erythromycin, tetracycline, chloramphenicol, and trimethoprim-sulfameth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Moreover, antibiotics can be purchased without prescription in the Philippines. For S. pneumoniae, all three invasive isolates were susceptible to penicillin, as reported in a previous study in Bohol, Philippines [61]. However, two cases with MRSA did not exhibited improvement during hospitalization.…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, antibiotics can be purchased without prescription in the Philippines. For S. pneumoniae, all three invasive isolates were susceptible to penicillin, as reported in a previous study in Bohol, Philippines [61]. However, two cases with MRSA did not exhibited improvement during hospitalization.…”
Section: Discussionsupporting
confidence: 80%
“…Other studies in asia have yielded mixed rates of antibiotic resistance, possibly influenced by local prescribing patterns. 5,10,13,[22][23][24][25] importantly, isolation of S. pneumoniae in this study may have been limited by the observed *Results from years 1 and 2 were annualized. The number of cases was the total of the number of cases captured during years 1 and 2.…”
Section: Discussionmentioning
confidence: 99%
“…In MLST, bacterial strains are identified by comparing the sequences of internal fragments of seven housekeeping genes (35). Six of the strains had been sequence typed in previous studies (12, 13) and 10 were analyzed at the National Public Health Institute, Helsinki, Finland, using the same method with minor modifications (8,52). PspA family typing.…”
Section: Methodsmentioning
confidence: 99%